Consumption and usage of information by chilean journalism students: The triumph of social media and preeminence of television in hedonistic and lightness consumption age - Avendaño Caneo, Daniel (2021)
The training of future journalists encourages knowledge and deepening of current affairs, for the construction of their speeches and contextualization of their media reality. Currently, new generations prefer digital platforms that become in a natural space to carry out activities. Therefore, it is important to understand which type of information they are consuming, which media is prefered to get information, how they are using and sharing it, and for what purposes, since these learners are the ones who, in the future, will act as builders of the media discourse. The objective of this research is to study the consumption and usage of current news of young journalism students from the Valparaíso Region in Chile. The study is quantitative in nature and the data collection is cross-sectional, carried out between August 2018and April 2019. The technique to collect the information is the survey. The universities selected for the study are Universidad Viña del Mar (UVM), Pontificia Universidad Católica de Valparaíso (PUCV) y Universidad Adolfo Ibáñez (UAI); all located in Región de Valparaíso, Chile.